Confusion in Gonadal Dysgenesis Terminology Persisting beyond Chicago Consensus Statement on Disorders of Sexual Development: Gonadal dysgenesis subtypes nomenclature - Ghahestani, Seyyed Mohammad; Karimi, Sara (Urology Journal, 2021)
Abstract: The terminology of gonadal dysgenesis conditions is considerably abstruse and variable. Despite some efforts in the 2006 Chicago Consensus Statement on DSD , it is still difficult to assign a category and name for some distinct conditions in this document. The rest of the literature has used redundant and variable words, e.g. partial, pure, and complete gonadal dysgenesis suffering equivocality and redundancy, aggravating this inconclusiveness. We attempted to highlight this problem and propose an easier terminology blueprint. Abstract: The terminology of gonadal dysgenesis conditions is considerably abstruse and variable. Despite some efforts in the 2006 Chicago Consensus Statement on DSD , it is still difficult to assign a category and name for some distinct conditions in this document. The rest of the literature has used redundant and variable words, e.g. partial, pure, and complete gonadal dysgenesis suffering equivocality and redundancy, aggravating this inconclusiveness. We attempted to highlight this problem and propose an easier terminology blueprint.